Analysis of the Effect of Heating Temperature on Tension Strength, Elongation and Function Clusters on Composite Tube Aerial Fiber Optic Cable G.652D-STEL-K-036-2012 - Herman, Herman Perez Purba; Budiarto, Budiarto; Sebayang, Melya Dyanasari (Journal of Technomaterial Physics, 2021)
The composite material of the fiber optic cable tube (G.652D-Stel-K-036-2012) or Polybutylene Terephthalate (PBT)-Master Batch MB) has been tested for tensile strength, elongation, and functional groups for fiber optic tube cladding materials. The purpose of this study was to determine the effect of heating temperatures of 2500C, 2550C, and 2600C on tensile strength, elongation, and functional groups in PBT-MB composite tube for fiber optic tube cladding material. The PBT-MB composite material was made by mixing PBT (80% by weight) with MB (20% by weight) in a ball mill. Then put together and processed into a tube on the extruder. Tensile and elongation strength was tested bytensile test, functional group test with FTIR, and humidity test. The results of the tensile test and elongation test increased with increasing heating temperature and still met the specified standard. The results of the functional group test showed that there was a CH bond from the PBT Tube at the highest wave peak, namely 2923.54 cm-11,725.10 cm-1,there was also a CH Aldehydes bond at a wavelength of 2852.19 cm-1,935.30 cm-1,916.02cm-1,873.59 cm -1,811.88 cm-1, the carbonyl bond C=C at a wavelength of 1708.61 cm-1,and the last is an Aromatic bond at a wavelength of 1504.20 cm-1. The chemical bonds in the test compounds were PBT-MB tube composites. From all the tests carried out, it was concluded that the variation of temperature on the manufacture of PBT-MB tube composites was very influential on the quality and still met the established standards.